Spontaneous Tumor Lysis Syndrome in a Patient with a Dedifferentiated Endometrial Adenocarcinoma. (27th August 2017) - Harada, Shinichi; Nagaharu, Keiki; Baba, Youichirou; Murata, Tetsuya; Mizuno, Toshiro; Kawakami, Keiki
Abstract : Tumor lysis syndrome (TLS) is an oncological emergency caused by massive cytolysis of malignant cells. This syndrome eventually induces metabolic abnormalities. TLS is observed mainly among tumors with rapid cell proliferation or high sensitivity to antineoplastic treatment. In rare cases, TLS occurs without any cytotoxic treatment. Previous reports have shown that alternative stress including proceeding infection or an operation might play a role in TLS. However, exact mechanism of spontaneous TLS remains unknown. Here, we describe a case of a 59-year-old woman who presented with dedifferentiated endometrial adenocarcinoma and developed TLS without any cytotoxic chemotherapy. Although spontaneous TLS in solid malignancies are extremely rare, clinicians should consider the possibilities of TLS especially in aggressive solid tumors.